2013
DOI: 10.1016/j.febslet.2013.02.001
|View full text |Cite
|
Sign up to set email alerts
|

HDAC6 promotes hepatocellular carcinoma progression by inhibiting P53 transcriptional activity

Abstract: a b s t r a c tHepatocellular carcinoma (HCC) is the most common type of liver cancer. HDAC6 is a transcriptional regulator of the histone deacetylase family, subfamily 2. Previous studies have shown that HDAC6 plays critical roles in transcription regulation, cell cycle progression and developmental events. However, its biological roles in the development of HCC remain largely unexplored. In the present study, we found that mRNA and protein levels of HDAC6 were up-regulated in HCC tissues and cell lines. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
63
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(67 citation statements)
references
References 30 publications
3
63
1
Order By: Relevance
“…Furthermore, clinical data showed that the level of HDAC6 in HCC was significantly lower than that in hepatitis and liver fibrosis. Opposite results have also been reported in HCC patients [19]. Upregulated HDAC6 were detected in HCC tissues and cell lines at the mRNA and protein levels.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…Furthermore, clinical data showed that the level of HDAC6 in HCC was significantly lower than that in hepatitis and liver fibrosis. Opposite results have also been reported in HCC patients [19]. Upregulated HDAC6 were detected in HCC tissues and cell lines at the mRNA and protein levels.…”
Section: Discussionmentioning
confidence: 53%
“…HDAC6 was shown to play an important role in cell proliferation through the NF-κB signaling pathway. Activation of NF-κB leads to the overexpression of HDAC6 at the transcriptional level since the promoter of HDAC6 contains a binding site of NF-κB [19]. Thus, the role of HDAC6 in the development of HCC is controversial, and the association of HDAC6 expression with GC is also unclear.…”
Section: Discussionmentioning
confidence: 99%
“…HDAC6 is particularly well suited for specific inhibition by being notably different from other HDACs with regard to protein structure, cellular localization, and its substrates, while still being involved in the regulation of cellular process like proliferation, migration, invasion and especially cellular stress response. 10,26,27 Moreover, HDAC6 has been reported to be overexpressed in a number of different cancer types such as ovarian, gastric, and breast cancer, oral squamous carcinoma and acute myeloid leukemia. 11,[28][29][30][31] In bladder cancer, HDAC6 expression and function has scarcely been investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly variable results on HDAC6 expression levels have been published for hepatocellular cancers. 27,37,38 Furthermore, HDAC6 has been reported to stimulate proliferation in the latter tumor type. In breast cancer, HDAC6 expression was likewise variable 29 and particularly strong in small tumors with low histological grade.…”
Section: Discussionmentioning
confidence: 99%
“…16,22,23 HDAC6 has also been studied in cancers because of its to ability to orchestrate a variety of cellular processes that are crucial for cancer pathogenesis. 24 Overexpression of HDAC6 has been demonstrated in hepatocellular carcinomas, 25 CTCL, 17 ALL, 22 and breast cancers. 26,27 Moreover, in contrast to increased Class I HDAC expression, which for the most part is an indicator of inferior survival, overexpression of HDAC6 has been largely associated with both improved overall (OS) and progression-free survival (PFS), including in studies of CTCL, 17 breast cancer, 26,27 lung cancer, 28 DLBCL, 20 and CLL.…”
Section: Introductionmentioning
confidence: 99%